A Study on foreign direct investment, the case of Cambodia - Seng, Sreng (KDI School, 2001)
The establishment of a free market economy in Cambodia has created a key condition for attracting foreign direct investment. Cambodia has not only the will but also the resources to constitute an attractive venue for foreign investment. The Royal Government of Cambodia recognizes that foreign investment is essential and that it can act as a catalyst for the development of the national economy. Therefore, Cambodia will make every effort to satisfy the needs of foreign investors. The Government of Cambodia is trying to create an institutional and regulatory framework, a stable policy, and a real free market-oriented system. However, to lay the foundation for the sustained inflow of foreign direct investment, the country must maintain a competitive edge and reduce the cost of doing business. The structural reforms will determine whether the country will attract the much-needed foreign investment funds This paper will examine the most critical reforms for promoting foreign direct investment in Cambodia. These include: providing a tax incentive system, providing a quality work force, improving the physical infrastructure, reducing red tape and bureaucratic corruption, as well as creating a stable political environment in the country. Not only is our government determined to improve the business climate for investors, but also to create a legislative structure that is supportive of business and investment. The implementation of reform measures has been intensified in the current legislative period. Cambodia will become a very competitive country for FDI, with a liberal business environment, low cost and hard working labor force. The Government of Cambodia will continue to attract companies from around the world to invest and to do business in Cambodia.
Thesis(Master) --KDI School:Master of Public Policy,2001